Kepemimpinan, Stres Kerja, Motivasi, Lingkungan Kerja dan Kinerja Kerja Karyawan - Putu Misiliana Christi W; Nyoman Sri Subawa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to analyze the influence of leadership, work stress, motivation, work environment and work performance at Airnav Indonesia Denpasar Branch. This study used simple random sampling technique on 68 respondents by taking respondents from permanent employees. The data used in this study were obtained from the measurement results of 68 employees (39 male employees and 29 female employees). The test was carried out by the PLS (Partial Least Square) method with the smartPLS program. The results of this study indicate that there is a significant influence of leadership on employee work performance. Job stress has a significant effect on employee work performance. Motivation has a significant effect on employee work performance. The work environment has a significant effect on employee work performance. Leadership has a significant effect on motivation. The work environment has a significant effect on the motivation of the employees of Airnav Indonesia Denpasar Branch. Keywords: Leadership, Job Stress, Motivation, Work Environment and Performance